Does Pictionary Game Effective for Students’ Speaking Skill? - Sholihatul Hamidah Daulay; Yani Lubis; Emeliya Sukma Dara Damanik; Rora Rizky Wandini; Fazar Azriani Putri (Journal of English Language Teaching and Linguistics, 2021)
Several problems of speaking in SMAN 6 Medan attracted researchers to conduct the research as an effort to help the students in language learning. Researchers attempted to see the effectiveness of Pictionary game toward English speaking skill. This Pictionary game is a simple game and applicable for all levels of students. The main function of this game is building of creative thinking, increasing of grammar, vocabulary and pronunciation, developing student’s bravery in expression of the ideas and creating of responsibility and cooperative towards the students. Because of this advantage, many researchers conducted this game on language learning such as the effect of Pictionary game on vocabulary mastery and researchers decided to see whether Pictionary game is effective for student speaking skill. This study is conducted by using an experimental design. In collecting of the data, researcher took pre-test and post-test from experimental and control class and examined them to see whether Pictionary game is effective or not. After analyzing of the data using of three tests, researchers found that the students’ score in experimental group was higher than control group in post-test. The calculation showed tobserved was 2.07. The degree of the freedom was 70 (df= n1 + n2 – 2) that means (df= 36 + 36 – 2) at the significance level 0.05, thus the critical score was 1.97. It can be concluded ttable was 1.97. then, the calculation of students’ scores shown that tobserved > ttable that means (Ha) was accepted, and (H0) was rejected. It means there is significance effect of the students’ speaking skill after treated by Pictionary game.